Islamisasi Jawa : Sayyid Ja’far Shadiq dan Menara Kudus Sebagai Media Dakwahnya - Muhammad Abdul Kharis (JURNAL INDO-ISLAMIKA, 2020)
The success of Muslims in spreading their teachings in the archipelago is very clearly seen by the evidence of the domination of Muslims in the archipelago today. This success is inseparable from the services of traders, preachers, kyai and teachers of the Koran. Including walisongo who has succeeded in introducing Islamic teachings to remote areas of Java. They use many approaches so that Islam can be well accepted by the surrounding community without war. One of them is by inserting Islamic values and teachings into the traditions and culture of Javanese society. Like Sunan Kudus, which is very tolerant of the culture that has been formed and rooted in the Kudus community. He adopted a lot of Hindu-Buddhist art and culture that has long been attached to the life of the Javanese people. Building the al-Aqsa Mosque that combines ancient Javanese mosque architecture with Indian Mughal architecture, the Kudus Tower is very similar to the Hindu Majapahit temple, places Buddhist teachings that do not conflict with Islamic teachings on the architecture of ablution and prohibits the slaughter of cows which are considered sacred by Hindus. All of this was done by Sunan Kudus to create Cultural Islam, Islam that interacts with culture so that it can be well received by the community without having to eliminate existing traditions and culture.